2006
DOI: 10.1096/fj.05-5032fje
|View full text |Cite
|
Sign up to set email alerts
|

Aβ induces cell death by direct interaction with its cognate extracellular domain on APP (APP 597–624)

Abstract: Amyloid β-peptide (Aβ) is postulated to play a central role in the pathogenesis of Alzheimer's disease. We recently proposed a pathway of Aβ-induced toxicity that is APP dependent and involves the facilitation of APP complex formation by Aβ. The APP-dependent component requires cleavage of APP at position 664 in the cytoplasmic domain, presumably by caspases or caspase-like proteases, with release of a potentially cytotoxic C31 peptide. In this study we show that Aβ interacted directly and specifically with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
124
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 44 publications
12
124
0
Order By: Relevance
“…Besides its role in A␤ peptide generation, APP protein is required for synaptic plasticity and other neuronal functions (Dawson et al, 1999;Priller et al, 2006). Moreover A␤ oligomers bind to the cognate A␤ extracellular domain of APP and generate a G protein-dependent intracellular signaling pathway through APP dimerization (Shaked et al, 2006(Shaked et al, , 2009. These data suggest that modifications of APP expression and/or processing could be involved in the cPLA 2 inhibition-mediated protection against A␤ oligomers neurotoxicity.…”
Section: Discussionmentioning
confidence: 98%
“…Besides its role in A␤ peptide generation, APP protein is required for synaptic plasticity and other neuronal functions (Dawson et al, 1999;Priller et al, 2006). Moreover A␤ oligomers bind to the cognate A␤ extracellular domain of APP and generate a G protein-dependent intracellular signaling pathway through APP dimerization (Shaked et al, 2006(Shaked et al, , 2009. These data suggest that modifications of APP expression and/or processing could be involved in the cPLA 2 inhibition-mediated protection against A␤ oligomers neurotoxicity.…”
Section: Discussionmentioning
confidence: 98%
“…We recently showed [7,32] that a significant component of Aβ toxicity in vivo may be dependent on the cleavage of APP at Asp664, since transgenic mice otherwise identical to a well-characterized model of AD, PDAPP mice [13,27], but carrying a mutation that obliterates the Asp664 cleavage site in APP [PDAPP(D664A)mice] continue to produce and deposit Aβ, but do not develop AD-like deficits. One potential link between Aβ production and APP Asp664 cleavage has been described, with the demonstration that Aβ binds APP and induces APP multimerization [2,19,21,22,34,35], leading in turn to cleavage of the APP cytosolic tail at Asp664 [21,22,34], followed by synaptic and neuronal damage [22,34].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter domain the dimerization appears to be mediated by the GXXXG motif near the luminal face of the transmembrane region (21, 23). In addition to promoting cell adhesion, APP dimerization has been proposed to increase susceptibility to cell death (20,24).Interestingly, by introducing cysteine mutations into the APP juxtamembrane region, it was shown that stable dimers through formation of these disulfide linkages result in significantly enhanced A␤ production (25). This finding is consistent with the observation that stable A␤ dimers are found intracellularly in neurons and in vivo in brain (26).…”
mentioning
confidence: 99%
“…In the latter domain the dimerization appears to be mediated by the GXXXG motif near the luminal face of the transmembrane region (21, 23). In addition to promoting cell adhesion, APP dimerization has been proposed to increase susceptibility to cell death (20,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation